FINANCIAL SECURITY OF TERRITORIAL COMMUNITIES AS A MAIN FACTOR FOR ENSURING THEIR SUSTAINABLE DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The peculiarities of the functioning of the united territorial communities, which were created in the process of budgetary and administrative decentralization in Ukraine, provide for the formation of a specific mechanism for attracting and using funds aimed at ensuring the sustainable development of these UTC. Therefore, the study of the features of financial security of financial flows of territorial communities becomes especially relevant in terms of the need to ensure their sustainable development. At the same time, one of the main criteria of financial security is that it should include a number of structural elements related to ensuring the tax content of local budgets, and should ensure the differentiation of sources of funds by expanding funding from private investors, which provides for private-public scheme. partnership.The article considers the specifics of financial decentralization and features of UTC budget formation in modern conditions. The principles of public-private partnership as a potential source of investment in the development of local communities are considered. Accordingly, it is the provision of proper cooperation with investors that allows local communities to increase the amount of funds that can be raised for projects related to their socio-economic development. Thus, the need to ensure transparent financial control over the receipt and use of these funds is a priority need of UTC in terms of ensuring their financial security. At the same time, although similar requirements apply to sources coming to the budgets of territorial communities, their use is definitely more transparent and controlled, as it takes place within the legally defined budget process.It is determined that ensuring the financial security of UTC is based on the observance of financial discipline by the executive bodies of communities, as well as on the basis of careful planning and control of revenues and expenditures to the UTC budget. It was investigated that the most important element of financial security of territorial communities is investment, as it is potentially able to provide the largest share of financial revenues for the needs of sustainable community development.
Keywords: UTC, financial security, investments, budget decentralization, finances of territorial communities.